2001
DOI: 10.1002/gcc.10026
|View full text |Cite
|
Sign up to set email alerts
|

Genomic gains and losses are similar in genetic and histologic subsets of rhabdomyosarcoma, whereas amplification predominates in embryonal with anaplasia and alveolar subtypes

Abstract: In this investigation, we selected PAX3/FKHR and PAX7/FKHR fusion transcript-positive and -negative alveolar rhabdomyosarcomas (ARMSs) and embryonal rhabdomyosarcomas (ERMSs) with and without anaplastic features, to ascertain genomic imbalance differences and/or similarities within these histopathologic and genetic rhabdomyosarcoma (RMS) variants. Comparative genomic hybridization (CGH) and fluorescence in situ hybridization (FISH) studies were performed on 45 rhabdomyosarcoma specimens consisting of 23 ARMSs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(100 citation statements)
references
References 31 publications
7
89
1
3
Order By: Relevance
“…Previous studies have shown that in contrast to non-anaplastic embryonal rhabdomyosarcomas, anaplastic tumors were characterized by more complex cytogenetic derangements with gene amplifications. 33,34 In keeping with this hypothesis, in our previous study, none of the well-differentiated liposarcomas was alternative lengthening of telomeres positive, but 30% (14/46) of the dedifferentiated liposarcomas were alternative lengthening of telomeres positive. 12 Except rare cases of myxoid liposarcoma and epithelioid hemangioendothelioma, 12,23 none of the gene fusion-associated sarcomas in our studies was ATRX-deficient or alternative lengthening of telomeres positive, indicating that alternative lengthening of telomeres is not an important telomeremaintenance mechanism for fusion-associated sarcomas.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have shown that in contrast to non-anaplastic embryonal rhabdomyosarcomas, anaplastic tumors were characterized by more complex cytogenetic derangements with gene amplifications. 33,34 In keeping with this hypothesis, in our previous study, none of the well-differentiated liposarcomas was alternative lengthening of telomeres positive, but 30% (14/46) of the dedifferentiated liposarcomas were alternative lengthening of telomeres positive. 12 Except rare cases of myxoid liposarcoma and epithelioid hemangioendothelioma, 12,23 none of the gene fusion-associated sarcomas in our studies was ATRX-deficient or alternative lengthening of telomeres positive, indicating that alternative lengthening of telomeres is not an important telomeremaintenance mechanism for fusion-associated sarcomas.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, the endogenous level of PAX3-FKHR in RH30, an ARMS cell line, is much higher than the level tolerated by the immortalized murine cells, suggesting that features within these ARMS cells attenuate the toxic effects and permit the cells to tolerate high level expression of PAX3-FKHR. In our search for candidate collaborating events, others and we have found that gene amplification occurs frequently in ARMS but not ERMS cells (Bridge et al, 2000(Bridge et al, , 2002. For example, the most frequently amplified chromosomal regions are 2p24 (involving MYCN) and 12q13-15 (involving MDM2 and CDK4) (Berner et al, 1996).…”
Section: Collaboration Among Two or More Oncogenes Or Tumor Suppressomentioning
confidence: 87%
“…10 Metaphase cells were banded with Giemsa trypsin, and the karyotypes were expressed according to the International System for Human Cytogenetic Nomenclature 1995. 11 …”
Section: Cytogenetic Analysismentioning
confidence: 99%